Project-Based Learning in Elementary Social Studies: A Literature Review on Effectiveness and Learning Outcomes - Burhan, Imron; Musfirah, Musfirah; Yuliani, Nur Fadny; Rachman, Siswati; Amriadi, Amriadi (PT. Riset Press International, 2025)
This article examines the impact of Project-Based Learning (PjBL) on elementary students’ learning outcomes in social studies through a literature review. The objective of this study is to identify how PjBL influences cognitive, affective, and psychomotor development, as well as creativity, motivation, collaboration, and communication skills. The method employed is a systematic analysis of 16 studies that investigate the implementation of PjBL in elementary classrooms. The findings indicate that PjBL enhances students’ understanding, retention, and application of material, promotes active engagement, and fosters 21st-century skills such as creativity and teamwork. The integration of interactive and visual learning media further strengthens learning effectiveness. However, challenges such as time constraints, large class sizes, and unequal group contributions may limit PjBL’s effectiveness if not properly addressed. Therefore, careful project planning, teacher guidance, and appropriate instructional media are essential to maximize PjBL’s benefits and support the holistic development of elementary students.